Uninterrupted control of coating thickness during the wear process of vehicle units - Makovkin, O.M.; Vychavka, A.A.; Valchuk, I.K. (Problems of Tribology, 2023)
In the course of this research in the field of automotive technology, systematic patterns and features of wear of structural materials with wear-resistant coatings that were applied using various technologies, depending on the change in friction modes, were revealed. Our research led to the identification of physical parameters of tribological properties and their changes in the friction process. An interesting property discovered in the course of our work is the fact that changing the contact area several times does not significantly affect the change in the friction coefficient. Instead, changes in the coefficient of friction are mainly related to the chemical composition of the secondary structures that are formed during friction. An important aspect of our findings is that the change in the coefficient of friction is usually due to the chemical composition of the secondary structures, which in turn depend on the chemical composition of the base material, the characteristics of the coating, the characteristics of the environment and the temperature conditions in the friction zone. An analysis of the chemical composition of secondary structures formed during friction was carried out, which allows for a deeper understanding of wear mechanisms and creates opportunities for optimizing materials and coatings in the field of automotive technology.